Intestinal permeability and contractility in murine colitis - M. E. van Meeteren; J. D. van Bergeijk; A. P. M. van Dijk; C. J. A. M. Tak; M. A. C. Meijssen; F. J. Zijlstra (Mediators of Inflammation)
We developed an in vitro organ bath method to measure permeability and contractility simultaneously in murine intestinal segments. To investigate whether permeability and contractility are correlated and influenced by mucosal damage owing to inflammation, BALB/c mice were exposed to a 10% dextran sulphate sodium (DSS) solution for 8 days to induce colitis. The effect of pharmacologically induced smooth muscle relaxation and contraction on permeability was tested in vitro. Regional permeability differences were observed in both control and 10% DSS-treated mice. Distal colon segments were less permeable to 3H-mannitol and 14C-PEG 400 molecules compared with proximal colon and ileum. Intestinal permeability in control vs. 10% DSS mice was not altered, although histologic inflammation score and IFN-γ pro-inflammatory cytokine levels were significantly increased in proximal and distal colon. IL1β levels were enhanced in these proximal and distal segments, but not significantly different from controls. Any effect of pharmacologically induced contractility on intestinal permeability could not be observed. In conclusion, intestinal permeability and contractility are not correlated in this model of experimentally induced colitis in mice. Although simultaneous measurement in a physiological set-up is possible, this method has to be further validated.